Participation, scenarios and pathways in long-term planning for climate change adaptation - Campos, Inês (2017)
This article describes a climate change adaptation planning process triggered by a group of researchers and stakeholders in a context where no collective responses or long-term plans for protecting a vulnerable coastal system had been initiated, despite local perceptions of vulnerability and risk. The case study shows the application of two methods: scenario workshops and adaptation pathways in the context of a participatory action research methodological design. Participatory action research and qualitative scenario methods are highlighted as accelerators of climate change adaptation processes by calling to action, facilitating and connecting diverse social groups with a stake in a long-term plan towards a more adapted society. The experience leads to the conclusion that planning climate change adaptation has to go far beyond the technical dimension and take into account those affected (in the present and the future) by decisions made. A holistic approach to climate change adaptation planning will depend on the interrelations of managerial and top-down approaches with localized initiatives driven through an inclusive and collective action research process.